Эффективность профилактического комплекса сопровождения ортодонтического лечения детей с флюорозом зубов = The effectiveness of preventive complex support orthodontic treatment of children with dental fluorosis - V. N. Gorohivsky (Kazimierz Wielki University, 2015)
Gorohivsky V N. Эффективность профилактического комплекса сопровождения ортодонтического лечения детей с флюорозом зубов = The effectiveness of preventive complex support orthodontic treatment of children with dental fluorosis. Journal of Education, Health and Sport. 2015;5(2):157-164. ISSN 2391-8306. DOI: 10.5281/zenodo.15715 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A157-164 https://pbn.nauka.gov.pl/works/541793 http://dx.doi.org/10.5281/zenodo.15715 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015.   УДК 616.31-085-053.2/.6-089.23+003.663.4 эффективность профилактического комплекса сопровождения ортодонтического лечения детей с флюорозом зубов   The effectiveness of preventive COMPLEX SUPPORT orthodontic treatment OF CHILDREN WITH dental fluorosis   В. Н. Горохивский V N Gorohivsky   ГУ «Институт стоматологии Национальной академии медицинских наук Украины» State Enterprise "Institute of Stomatology National Academy of Medical Sciences of Ukraine", Odessa, Ukraine               Реферат Показано, что комплексные патогенетически обоснованные профилактика и лечение основных стоматологических заболеваний при ортодонтическом лечении зубо-челюстных аномалий у детей с флюорозом зубов улучшает показатели твердых тканей зубов, тканей пародонта, уровня гигиены полости рта, нормализует функциональные реакции, ответственные за гомеостаз ротовой жидкости, улучшает барьерную защиту десны от проникновения красителей и, следовательно, микроорганизмов.     Ключевые слова: флюороз зубов, ортодонтическое лечение, лечебно-профилактический комплекс.   Abstract Orthodontic movement of teeth in children living in areas of endemic fluorosis requires the development of specific pathogenetically grounded complexes preventive maintenance of orthodontic treatment. The objective of this work was to evaluate the effectiveness of the integrated prevention and treatment of major dental diseases in children with dental fluorosis in orthodontic treatment of dento-alveolar anomalies. Materials and methods. Clinical trials involved 47 children with dental fluorosis age 12-14 years. In the comparison group performed sanitation and professional hygiene. Children of the main group additionally received prophylactic complex, which included detoxicant, adaptogenic, antioxidant and other drugs. Results. Conclusions. It is shown that the complex pathogenetically-based prevention and treatment of major dental diseases in orthodontic treatment of dento-alveolar anomalies in children with dental fluorosis improves indices of hard tissues teeth, periodontal tissues, oral hygiene, normalizes functional reactions responsible for the homeostasis of oral liquid, improves the barrier gum protection against penetration of dyes and hence microorganisms. Keywords: dental fluorosis, orthodontic treatment, therapeutic and preventive complex.